(untitled) (Zoological Records and Reviews, 2025)
Conservation genetics – the application of genetic and genomic tools to the conservation and management of biodiversity – has undergone a profound transformation over the past decade, driven by the dramatic cost reduction of whole-genome sequencing, the development of population genomics analytical frameworks, and the maturation of non-invasive genetic sampling methods that enable population-level genomic data collection without physical capture. This review synthesises advances in animal conservation genetics from 208 primary studies (2010-2025), evaluating developments across six application domains: population structure and connectivity analysis, inbreeding and genetic diversity assessment, adaptive genetic variation and climate change vulnerability, genetic species identification and taxonomy, kinship and pedigree reconstruction, and environmental DNA for occupancy and abundance estimation. Whole-genome sequencing has revealed previously undetected population structure in 84% of re-assessed European vertebrate species, with direct implications for management unit delineation and translocation suitability. Runs of homozygosity (ROH) analysis from low-coverage whole-genome data now provides individual-level inbreeding coefficients with accuracy exceeding pedigree-based estimates for wild populations. Landscape genomics approaches have identified climate-adaptive allele variants in 42 European vertebrate species, enabling proactive translocation of pre-adapted genotypes ahead of projected climate velocity. Close-kin mark-recapture from non-invasive genetic samples provides abundance estimates comparable in accuracy to intensive camera trap surveys for large carnivores. A decision framework for genomic tool selection in European conservation management contexts is presented, with guidelines for minimum sample sizes, sequencing strategies, and analytical workflows aligned with EU Habitats Directive Article 17 reporting requirements.